Bohemian Baroque : Czech Musical Culture and Style, 1600-1750 - Rawson, Robert G. (Cambridge University Press, 2013)
Traditional polemical histories of Bohemia and Moravia identify the period from the early seventeenth to the second half of the eighteenth-century as a 'period of darkness' - particularly in terms of Czech-language culture. This book challenges that interpretation from the perspective of musical culture and demonstrates that this was in fact a vibrant, productive and innovative period, both for music in the Czech language and instrumental music. Focussing on the distinctive nature of Czech-language education and devotion along with Germanic traditions and the prominent role of rural life in sh.